PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max L.) TERHADAP PEMBERIAN VERMIKOMPOS DAN BIOCHAR DI TANAH ULTISOL - Elisa Ester Sirait; Nelvia Nelvia; Hafiz Fauzana (Jurnal Solum, 2020)
The use of organic matter in agricultural production is important in increasing crop production, especially in Ultisols. This study aimed to study the interaction between vermicompost and biochar on the growth and yield of soybean (Glycine max L.) in Ultisols. The research was carried out in the experimental station of the Faculty of Agriculture, Riau University, Bina Widya Tampan campus, Pekanbaru from July - September 2018. The research used factorial design form in a completely randomized design. The first factor is vermicompost which consists of 4 levels (doses of 0, 25, 50 and 75 g of polybag-1) while the second factor is biochar consisting of 4 levels (doses of 0, 25, 50 and 75 g of polybag-1) for each combination repeated 4 times. The parameters observed were the number of effective roots, proportion of effective nodules, plant height, number of primary branches, age of plants, age of harvest, proportion of well-fused pods, number of seeds, seed weight and weight of 100 seeds. The results showed that the interaction of vermicompost at a dose of 25 g.polybag-1 following a dose of 50 g.polybag-1 biochar increased the number of effective root nodules, the proportion of effective root nodules, the number of primary branches, the proportion of pithy pods, and accelerated plant age and soybean plant age compared without treatment but not significantly compared to other combinations.Key words : Soybean, vermicompost, biochar